The Discourse of Resistance in The Short Story "Siapa Kirim Aku Bunga?" - Diki Febrianto; M. Yoesoef (Pioneer: Journal of Language and Literature, 2023)
This study uses a corpus of short stories entitled Siapa Kirim Aku Bunga? by Eka Kurniawan, which contains issues of postcolonialism through mimicry, ambivalence, and hybridity of the Si Gadis Penjual Bunga’s character, which then shows the existence of a discourse of resistance. This study aims to dismantle the strategy of resistance through mimicry, ambivalence, and hybridity in the short story Siapa Kirim Aku Bunga? by Eka Kurniawan. This research is qualitative, using the hermeneutic method. The research begins with understanding the text, then interpreting it to show and explain the existence of mimicry, ambivalence, and hybridity with descriptive methods. The approach used in this research is post-colonialism. The show that mimicry, ambivalence, and hybridity through European dress are a strategy in carrying out a discourse of resistance by the colonized to the colonialists. This resistance refers to the dark story of the Indonesian people regarding the disposal of indigenous people who were sent and exiled to Boven Digoel. Through the metaphor of flowers, this work depicts the deep sadness of that time.